PERLINDUNGAN HUKUM TERHADAP INVENSI KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) DI ERA REVOLUSI INDUSTRI4.0 DAN SOCIETY 5.0 BERDASARKAN PERSFEKTIF UNDANG-UNDANG NOMOR 13 TAHUN 2016 TENTANG PATEN - Ira Sopiyah; Rumainur (JOURNAL OF LAW AND NATION, 2025)
Legal protection of artificial intelligence inventions in the Industrial Revolution 4.0 and Society 5.0 eras is becoming very important along with the rapid development of technology and innovation. This study analyzes how Law Number 13 of 2016 concerning Patents provides a legal basis for the protection of inventions involving AI. With a normative analysis approach, this study identifies challenges and opportunities in patent regulations for AI-based innovations, including criteria for novelty, inventive step, and industrial application. The results of the study show that although the Patent Law has provided a basic framework, there are still shortcomings in accommodating the unique characteristics of AI, such as learning and adaptation capabilities. Therefore, the development of more flexible and responsive regulations is needed to protect intellectual property rights in the context of this advanced technology. This study is expected to contribute to the formulation of more effective legal policies for AI innovation in Indonesia.